Modulating Central Gain in Tinnitus: Changes in Nitric Oxide Synthase in the Ventral Cochlear Nucleus - Coomber, Ben; Kowalkowski, Victoria L.; Berger, Joel I.; Palmer, Alan Richard; Wallace, Mark Nelson (Frontiers in Neurology, 2015)
A significant challenge in tinnitus research lies in explaining how acoustic insult leads to tinnitus in some individuals, but not others. One possibility is genetic variability in the expression and function of neuromodulators – components of neural signalling that alter the balance of excitation and inhibition in neural circuits. An example is nitric oxide (NO) – a free radical and potent neuromodulator in the mammalian brain – that regulates plasticity via both presynaptic and postsynaptic mechanisms. Changes in NO have previously been implicated in tinnitus generation, specifically in the ventral cochlear nucleus (VCN). Here, we examined nitric oxide synthase (NOS) – the enzyme responsible for NO production – in the guinea pig VCN following acoustic trauma. NOS was present in most cell types – including spherical and globular bushy cells, small, medium and large multipolar cells, and octopus cells – spanning the entire extent of the VCN. The staining pattern was symmetrical in control animals. Unilateral acoustic over-exposure (AOE) resulted in marked asymmetries between ipsilateral and contralateral sides of the VCN in terms of the distribution of NOS across the cochlear nuclei in animals with behavioural evidence of tinnitus: fewer NOS-positive cells and a reduced level of NOS staining was present across the whole extent of the contralateral VCN, relative to the ipsilateral VCN. The asymmetric pattern of NOS-containing cells was observed as early as one day after AOE and was also present in some animals at 3, 7 and 21 days after AOE. However it was not until eight weeks after AOE, when tinnitus had developed, that asymmetries were significant overall, compared with control animals. Asymmetrical NOS expression was not correlated with shifts in the threshold hearing levels. Variability in NOS expression between animals may represent one underlying difference that can be linked to whether or not tinnitus develops after noise exposure.